PENGEMBANGAN BAHAN AJAR KIMIA BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN METAKOGNISI - Nishfiya Ramdoniati; Muntari Muntari; Saprizal Hadisaputra (Jurnal Penelitian Pendidikan IPA, 2019)
This study aims to development of chemical learning material based PBL to improve metacognition skills of students on the material of electrolyte and nonelectrolyte solutions. The type of research used is Research and Development (R & D) with the modification of 4D model into 3D which consists of define, design and develop. The results showed that the average score of the feasibility of learning materials of 3.18 with medium category, The average score of teacher response and the response of learners is 3.58 with the practical category. The effectiveness data of learning materilas based PBL was obtained from N-Gain metacognition skill score of 0.51 in the medium category, meaning that chemical learning materials based PBL is effective to improve metacognition skills on the topic of electrolyte and nonelectrolyte solutions. Keyword: Chemical learning material, problem based learning, metacognitive skills.